Produção de extrato de Artemisia annua L. asteraceae e o uso deste na obtenção de formas farmacêuticas sólidas - Silva, Elviscley de Oliveira (2015)
Artemisia annua is originally from China, where it is used over two thousand years in the treatment of various diseases, especially malaria. The chemical compound of main therapeutic importance is artemisinin, a sesquiterpene lactone with an endoperoxide ring, responsible for potent antimalarial activity of the plant. Only one study about the production of pharmaceutical forms to A. annua extract was found in the literature. The main objective of this work was to obtain a concentrated extract of aerial parts of A. annua and using this for production of phytomedicines. The vegetal drug showed adequate physicochemical properties and artemisinin content of 1.15 ± 0.05 %. All assays of the analytical method validation were in specifications with LOD and LOQ of 1.3 mg/ml and 4.0 mg/ml of artemisinin, respectively. The partial validations for analyze of tablets, capsules and pellets were within the specifications in selectivity, linearity and repeatability testing. The vegetable drug was percolated and obtained 80% yield artemisinin extraction. Four kilograms of vegetable drugs yielded 2.5 liters of concentrated extract with 1.47% (w/v) of artemisinin and 30.78% (w/w) of dry residue. This was used to produce pellets, tablets and capsules, which contained 8.1 mg, 9.6 mg and 10.0 mg of artemisinin, respectively. All showed determination weight and content uniformity within specifications, demonstrating that the manufacture from the concentrated extract was effective in relation to the desired dosage artemisinin. The tablets showed immediate dissolution at pH 6.8 only. At pH 1.2 disintegrated in 60 minutes, releasing 85.2% of artemisinin against 99.8% of the capsules at 20 min, and 103.3% of pellets at 30 minutes. The dissolution profile of the capsules and pellets showed a very fast immediate dissolution at pH 1.2 and 6.8. Therefore, the dissolution efficiency (DE) of the tablets was lower than that of the capsules and pellets, for both pH values. The value F2 indicated a difference between the profiles of the tablets at different pH values, with the smallest dissolution in pH 1.2. The formulations prepared in this study demonstrated how the concentrate extract of A. annua can be used to manufacture phytomedicines content artemisinin near the expected and other appropriate physico-chemical properties.